Resigned marketing in light of the circular economy: an empirical Investigation of Malaysia and Pakistan - Jan, Muhammad Tahir (Association Res Militaris, 2022)
Due to the industrial revolution, the production and consumption of products are at an all-time high, resulting in environmental decimation. This damage to the environment can be reduced by following the “Circular Economy” concept. This concept focuses on introducing innovative systems to reduce or even eliminate harm to the environment at large. As marketing encourages people (consumers) to buy and use the products repeatedly, the impact is devastating. This study, therefore, attempts to introduce and empirically test a redesigned marketing philosophy with the inclusion of a circular economy in the established model of the Theory of Planned Behavior. Data were collected and subsequently tested from two countries, namely, Malaysia and Pakistan. The results of this study can be used as a guideline by marketers and policymakers to devise innovative environmentally friendly strategies.